Engagement factors affect academic success through study approaches among physical education and sport university students: a mediation analysis - Tannoubi, Amayra; Bonsaksen, Tore; Mørk, Gry; Ahmedov, Farruh; Setiawan, Edi; Azaiez, Fairouz (Frontiers in Education, 2025)
IntroductionUniversity students should engage with the study and ensure they adopt productive study approaches, but the nature of relationships between engagement and study approaches are under-researched. The study aimed to investigate how emotional, cognitive, and behavioral engagement affect academic success through study approaches among physical education and sports students.MethodsOnline forms were submitted by 488 students in physical education and sports (age range 19–25 years, Mean = 21 ± 1.5 year). They completed surveys regarding their academic engagement, study approaches, and grade point average (GPA). Analyses of associations were conducted through linear regression analysis and mediation analysis.ResultsResults from the linear regression analysis showed correlations between academic engagement factors, study approach variables, and GPA, with higher GPA correlating with higher scores on behavioral engagement, cognitive engagement, surface theory task, and deep theory task, and with lower scores on surface practical task. The analysis of total and direct effects revealed positive associations between all academic engagement factors and GPA. Emotional engagement exhibited a positive association with GPA mediated by study approaches. All engagement dimensions appear to influence academic success among these students.ConclusionThe influence of emotional engagement on academic success appears in part to be operating through its effects on study approaches. The study can enable educators in monitoring and enhancing student engagement, thereby supporting students in their pursuit of high academic performance in physical education and sport.